Assessment of the effect of different forms of Inconel 625 alloy feedstock in Plasma Transferred Arc (PTA) additive manufacturing (vol 98, pg 1695, 2018) - Cardozo, Eloisa Pereira; Rios Contesse, Sergio Eduardo; Ganguly, Supriyo; D'Oliveira, Ana Sofia C. M. (My University, 2018)
The original version of this article contained a mistake. Fig. 8 in the original article is incorrect. The correct image is shown below.
Keywords: Mistake; Inconel; Plasma arc welding; Inconel 625